Molecular adsorption by biochar produced by eco-friendly low-temperature carbonization investigated using graphene structural reconfigurations. Issue 1 (2nd January 2022) - Sato, Kiminori; Yamamoto, Akinori; Dyballa, Michael; Hunger, Michael
ABSTRACT: Biochar is a promising material for environmental amendment. However, the adsorption mechanism of nitrogen-based ionic species, particularly the pH dependence, is still under debate because of its high susceptibility to experimental conditions. In this study, the adsorption of ammonium sulfate by rice-husk biochar produced by low-temperature carbonization as an eco-friendly approach was studied using Fourier-transform infrared (FT-IR) spectroscopy, 13 C magic-angle spinning (MAS) nuclear magnetic resonance (NMR), and open-space analysis using positrons coupled with molecular simulations. In the aqueous solution with pH of 5.38, graphenes are isolated exposing fresh surfaces, which physisorb N H 4 + via interaction with π electrons rather than surface functional groups. Furthermore, the low-temperature carbonization leads to a lower degree of graphitization with grain boundary defects in graphene, triggering the fracture of graphene during the shaking process in an aqueous solution. S O 4 2 − physisorption occurs as an outer-sphere surface complex on the positive charge caused by a charge transfer of ∼2.5% from the terminal hydrogen at the graphene edge. A decrease in aqueous pH by ∼0.7% significantly changes the above adsorption properties both on the surfaces and at the edges: diminishment of physisorption and transition to chemisorption by the formation of an inner-sphere surface complex. GRAPHICAL ABSTRACT: UF0001